Enhanced sequential osteosarcoma therapy using a 3D-Printed bioceramic scaffold combined with 2D nanosheets via NIR-II photothermal-chemodynamic synergy - Guangyu Jian; Si Wang; Xinlu Wang; Qinyi Lu; Xingyu Zhu; Shucheng Wan; Shan Wang; Dize Li; Chao Wang; Qingqing He; Tao Chen; Jinlin Song (Bioactive Materials)
Background: Osteosarcoma (OS) is a malignant tumor originating from primitive mesenchymal cells, characterized by rapid metastasis, high invasiveness, and significant mortality. The primary challenges in OS management include the effective elimination of residual tumor cells to prevent recurrence and the repair of extensive bone defects caused by surgical intervention. Objective: This study aims to develop an innovative biomimetic 3D-printed bioactive glass ceramic (BGC) scaffold modified with two-dimensional nanosheets to address both tumor ablation and bone tissue repair. Materials and methods: The nanosheets were constructed via ellagic acid (EA) and ruthenium (Ru) coordination, leveraging the non-topological adhesion properties of catechol in EA to deposit the nanosheets onto the BGC scaffold (EARu-BGC). The therapeutic effects of EARu-BGC were evaluated in vitro and in vivo. Results: EARu-BGC sequentially responds to the local microenvironment during OS treatment. During the tumor ablation phase, EARu-BGC induced ferroptosis through the synergistic effects of photothermal and chemodynamic therapy, achieving over 90 % tumor cell ablation and significantly inhibiting tumor volume and weight. In the bone tissue repair phase, EARu-BGC exhibited adaptive ROS scavenging and facilitated a pro-healing microenvironment, promoting osteogenic differentiation. The gradual degradation of the BGC scaffold provided essential minerals and space for new bone formation. In vivo experiments demonstrated that EARu-BGC significantly enhanced osteogenesis, increasing the trabecular number to 1.51 ± 0.15/mm and reducing trabecular separation to 1.50 ± 0.04 mm. Conclusion: The EARu-BGC scaffold presents a promising multifunctional platform for OS treatment by effectively balancing antitumor efficacy with bone repair capabilities.